Spectral, Electrochemical and Molecular Modeling Studies of Some 3 (2 Hydroxy benzalhydrazino-4-thiazolyl)coumarins - N. Raju; A. Ramachandraiah (E-Journal of Chemistry)
Spectral, cyclic voltammetric and molecular modeling studies have been carried out on some 3-(2-hydroxybenzalhydrazino-4-thiozolyl)coumarins (1), to understand their solution and electrochemical characteristics. These investigations reveal structural alterations in the conjugates of their acid-base equilibria as indicated by considerable bathochromic shift in electronic spectra and changes in electron transfer properties with rise in pH. The pKa values and electrochemical data such as Ep, ip, αna, k ° h, etc., of 1 were evaluated. Further, the compound 1 is found to be good chelating ligands. Molecular modeling studies were also performed to correlate the spectral and electrochemical observations. Voltammetric analysis of 1 is also presented.